Positive Trend Inflation and Determinacy in a Medium-Sized New Keynesian Model - Jonas E. Arias; Guido Ascari; Nicola Branzoli; Efrem Castelnuovo (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper studies the challenge that increasing the inflation target poses to equilibrium determinacy in a medium-sized New Keynesian model without indexation fitted to the Great Moderation era. For moderate targets of the inflation rate, such as 2 or 4 percent, the probability of determinacy is near one conditional on the monetary policy rule of the estimated model. However, this probability drops significantly conditional on model-free estimates of the monetary policy rule based on real-time data. The difference is driven by the larger response of the federal funds rate to the output gap associated with the latter estimates.
Keywords: E52; E30; C22; 330; trend inflation; determinacy; monetary policy